1999
DOI: 10.1161/01.cir.99.18.2427
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Head-Up Tilt Testing and ATP Testing in Assessing the Mechanisms of Vasovagal Syndrome

Abstract: Results suggest tilt and ATP tests individually and jointly determine the mechanism of vasovagal symptoms in most patients and that vagal cardiac inhibition increases with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
0
16
0
8
Order By: Relevance
“…[3][4][5]10 Furthermore, the present study suggests that these patients can be identified, and if further studies could show that syncope is reproduced by exogenous adenosine infusion in these patients, this will favor a causal mechanism of elevated adenosine plasma levels.…”
Section: Study Limitationsmentioning
confidence: 56%
See 3 more Smart Citations
“…[3][4][5]10 Furthermore, the present study suggests that these patients can be identified, and if further studies could show that syncope is reproduced by exogenous adenosine infusion in these patients, this will favor a causal mechanism of elevated adenosine plasma levels.…”
Section: Study Limitationsmentioning
confidence: 56%
“…Several investigators have hypothesized that adenosine is an important modulator that can trigger vasovagal syncope in susceptible patients. [3][4][5]9 Indeed, the injection of exogenous adenosine or ATP during head-up tilt testing provoked a vasovagal response in those patients with syncope, with a yield comparable to that of isoproterenol. [3][4][5]10 Adenosinesensitive syncope has been identified as a cause of syncope in some patients with an abnormal response to an ATP test.…”
Section: Saadjian Et Al Endogenous Adenosine In Vasovagal Syncopementioning
confidence: 99%
See 2 more Smart Citations
“…Both ATP and tilt testing were performed in patients with unexplained syncope in two studies [208,209] . Although some overlap of positive responses was observed, this was limited to no more than 20% of cases.…”
Section: Relationship Between Atp and Tilt Testingmentioning
confidence: 99%